2011
DOI: 10.1117/12.885880
|View full text |Cite
|
Sign up to set email alerts
|

Si pillar structured thermal neutron detectors: fabrication challenges and performance expectations

Abstract: Solid-state thermal neutron detectors are desired to replace 3 He tube tube-based technology for the detection of special nuclear materials. 3He tubes have some issues with stability, sensitivity to microphonics and very recently, a shortage of 3 He. There are numerous solid-state approaches being investigated that utilize various architectures and material combinations. Our approach is based on the combination of high-aspect-ratio silicon PIN pillars, which are 2 µm wide with a 2 µm separation, arranged in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Semiconductor with a thin-film coating of neutron reactive material deposited on a planar rectifying diode have been investigated for the past few decades as a potential neutron detector technology while maintaining high gamma-ray rejection characteristics [1][2][3]. MSNDs were developed as a means of increasing the relatively low efficiency of the planar thin-film-coated devices (typicallyo4-5% intrinsic) up to their theoretical maximums above 40% intrinsic detection efficiency for single 0.5-mm thick devices [4][5][6][7][8][9][10][11][12][13][14][15][16] while maintaining gamma-ray rejection ratios (GRR) of 10 À 6 or better [12]. The increase in intrinsic neutron detection efficiency stems from the two primary benefits of perforating a semiconductor diode; increased neutron absorption and increased probability of interaction of the charged neutron reaction products in the semiconductor diode.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor with a thin-film coating of neutron reactive material deposited on a planar rectifying diode have been investigated for the past few decades as a potential neutron detector technology while maintaining high gamma-ray rejection characteristics [1][2][3]. MSNDs were developed as a means of increasing the relatively low efficiency of the planar thin-film-coated devices (typicallyo4-5% intrinsic) up to their theoretical maximums above 40% intrinsic detection efficiency for single 0.5-mm thick devices [4][5][6][7][8][9][10][11][12][13][14][15][16] while maintaining gamma-ray rejection ratios (GRR) of 10 À 6 or better [12]. The increase in intrinsic neutron detection efficiency stems from the two primary benefits of perforating a semiconductor diode; increased neutron absorption and increased probability of interaction of the charged neutron reaction products in the semiconductor diode.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of current limits for building a high-efficiency, low-cost neutron detector using standard commercial methods was developed, and many in the science community are developing strategies to operate within, and overcome, those limits. Bellinger "Characteristics" 2010, Brickner 2010, Nikolić 2010, Raphaelian 2010, McElfresh 2011, Nikolić 2011, Bellinger 2012. When the 10 B(n,α) 7 Li reaction is used for neutron detection, the key is to capture as many of the α-particles, and as much of the initial particle energy, as possible.…”
Section: Mark Raphaelian 1a and Michael Mcelfresh Amentioning
confidence: 99%
“…Specifically, colloidal nanoparticles and nanowires are attractive as they take advantage of quantum confinement effects, are easy to fabricate, have a high surface-to-volume ratio, and are relatively low cost. Furthermore, our research to create metalsemiconductor-metal (MSM) devices demonstrated that the current carrying mechanism creates a high internal photoconductive gain due to the presence of oxygen-related hole-trap states at the nanoparticle's surface and the high resolution of interdigitated electrodes (Qin "Comparison" 2010, Qin "Metalsemiconductor-metal" 2010, Shao 2011, Shao "Optical" 2012, Shao "High Responsivity" 2012. Recently, detectors using zinc oxide (ZnO) nanowires were demonstrated (Shao "Heterojunction" 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The second route by vapor-liquid-solid growth has risen in popularity as a low-cost alternative. The most common techniques are nanosphere lithography (NSL) [15][16][17][18] and block copolymer lithography [19,20]. Nanospheres or nanopaticles were introduced onto the substrate to create different nanostructures by self-assembly [21,22].…”
Section: Introductionmentioning
confidence: 99%